OC-014 Extra Wide Angle View Colonoscope (EWAVE) has Superior Polyp Detection Rate When Compared to a Standard Colonoscope (SD): A Randomised Tandem Pre-Clinical Study. (17th August 2016) - Rameshshanker, R; Wilson, A; Tekkis, P; Saunders, BP
Abstract : Introduction: Colonoscopy screening with the removal of adenomas has been the preferred and most effective strategy to prevent colorectal cancer (CRC). However adenomas are often missed during colonoscopic examination, particularly on the proximal sides of folds and at the flexures. The prototype (EWAVE) Extra Wide Angle View colonoscope (Olympus, Tokyo, Japan) has a 147°–235° angle lateral/backward view lens and a standard 140° angle forward view lens. Views from both lenses are constructed and displayed as a single image. By improving visualisation behind the folds and flexures this new scope could increase the polyp detection rate (PDR). Objective is to compare the polyp detection rate between EWAVE and a standard colonoscope in a colonic model with simulated polyps. Methods: Two colorectal (Koken, Japan) rubber colon models were prepared with 18 and 20 polyps of different size (520 mm) at various locations. Seventeen endoscopists, 14 gastroenterology trainees and 3 nurse endoscopists with varying levels of experience performed back to back examinations with the standard colonoscope and EWAVE scope. The order which they performed the procedure (i.e. EWAVE or SD first) was randomised using concealed envelopes. In order to minimise type 2 error, on the 2 nd model the endoscopists performed the procedure in reverse order. Results: There was no significant difference in mean insertion time (p = 0.8) or withdrawal time (p = 0.29) between EWAVE and standard colonoscope (Figure 1). Mean simulated PDR was significantly higher with EWAVE examination when compared to standard colonoscopic examination in both models (p = 0.026 and <0.0001). Mean simulated PDR was significantly higher with EWAVE in comparison to the standard colonoscope for polyps in the mid transverse colon (79.4% vs 32.3%, p = 0.0002) and mid sigmoid colon (82.3% vs 52.9%, p = 0.0186). When the examination was carried out with the standard colonoscope followed by EWAVE, PDR was significantly higher in both models (p = 0.045 for model 1 and p < 0.0001 for model 2). More significantly no difference was observed when the procedure was performed in the reverse order (p = 0.28 for model 1 and p = 0.08 for model2). Conclusion: Our non-clinical study showed significantly higher polyp detection rates with the novel extra wide angle colonoscope when colonoscopy was performed by moderately experienced colonoscopists. Further clinical trials appear warranted. Disclosure of Interest: None Declared